A long-term study on the prevalence of shiga toxin-producing Escherichia coli (STEC) on four German cattle farms. - Geue, L. (Cambridge University Press, 2002)
The occurrence of Shiga toxin-producing Escherichia coli (STEC) was studied on four cattle farms. STEC were detected in 29-82% of the cattle. STEC with additional EHEC markers were detected on all farms. The occurrence of the complete virulence marker pattern (stx1 and/or stx2, eae, EHEC(hlyA), katP, espP) was correlated with the presence of known STEC serotypes. STEC O26:H11 and O165:H25 with the complete pattern of virulence markers were the most prevalent. STEC O157 (H7/H-) STEC O103:H2 and STEC O145:H- were found sporadically. Five clonal subgroups of the STEC O26:H11 isolates were identified by pulsed-field gel electrophoresis. STEC O26:H11 were present in three groups of cattle. This serotype was detected in a single group over the entire fattening period. Most STEC O26:H11 with the complete pattern of potential virulence markers were found in clinically healthy cattle. These animals may represent a risk factor for farmers and consumers.